Sex Differences in Cardiovascular Effectiveness of Newer Glucose‐Lowering Drugs Added to Metformin in Type 2 Diabetes Mellitus - Valeria Raparelli; Malik Elharram; Cristiano S. Moura; Michal Abrahamowicz; Sasha Bernatsky; Hassan Behlouli; Louise Pilote (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Randomized controlled trials showed that newer glucose‐lowering agents are cardioprotective, but most participants were men. It is unknown whether benefits are similar in women. Methods and Results Among adults with type 2 diabetes mellitus not controlled with metformin with no prior use of insulin, we assessed for sex differences in the cardiovascular effectiveness and safety of sodium‐glucose‐like transport‐2 inhibitors (SGLT‐2i), glucagon‐like peptide‐1 receptor agonists (GLP‐1RA), dipeptidyl peptidase‐4 inhibitors, initiated as second‐line agents relative to sulfonylureas (reference‐group). We studied type 2 diabetes mellitus American adults with newly dispensed sulfonylureas, SGLT‐2i, GLP‐1RA, or dipeptidyl peptidase‐4 inhibitors (Marketscan‐Database: 2011–2017). We used multivariable Cox proportional hazards models with time‐varying exposure to compare time to first nonfatal cardiovascular event (myocardial infarction/unstable angina, stroke, and heart failure), and safety outcomes between drugs users, and tested for sex–drug interactions. Among 167 254 type 2 diabetes mellitus metformin users (46% women, median age 59 years, at low cardiovascular risk), during a median 4.5‐year follow‐up, cardiovascular events incidence was lower in women than men (14.7 versus 16.7 per 1000‐person‐year). Compared with sulfonylureas, hazard ratios (HRs) for cardiovascular events were lower with GLP‐1RA (adjusted HR‐women: 0.57, 95% CI: 0.48–0.68; aHR‐men: 0.82, 0.71–0.95), dipeptidyl peptidase‐4 inhibitors (aHR‐women: 0.83, 0.77–0.89; aHR‐men: 0.85, 0.79–0.91) and SGLT‐2i (aHR‐women: 0.58, 0.46–0.74; aHR‐men: 0.69, 0.57–0.83). A sex‐by‐drug interaction was statistically significant only for GLP‐1RA (P=0.002), suggesting greater cardiovascular effectiveness in women. Compared with sulfonylureas, risks of adverse events were similarly lower in both sexes for GLP‐1RA (aHR‐women: 0.81, 0.73–0.89; aHR‐men: 0.80, 0.71–0.89), dipeptidyl peptidase‐4 inhibitors (aHR‐women: 0.82, 0.78–0.87; aHR‐men: 0.83, 0.78–0.87) and SGLT‐2i (aHR‐women: 0.68, 0.59–0.78; aHR‐men: 0.67, 0.59–0.78) (all sex–drug interactions for adverse events P>0.05). Conclusions Newer glucose‐lowering drugs were associated with lower risk of cardiovascular events than sulfonylureas, with greater effectiveness of GLP‐1RA in women than men. Overall, they appeared safe, with a better safety profile for SGLT‐2i than for GLP‐1RA regardless of sex.